Memory and its neural basis - McClelland, James (Henry Stewart Talks, 2010)
What is a memory?, Multiple memory systems approach to the neural basis of memory, A taxonomy of memory, The complementary learning systems theory, The neuro-mechanistic theory: processing and learning in neocortex, Complementary learning system in the hippocampus, Neurophysical evidence, Complementary learning and representation, Inner structures of the hippocampus, Knockout NMDA receptors in dentate gyrus, Collaboration of hippocampus and neocortex
Updated at 2020/12/16